3D porous Cu@Cu2O films supported Pd nanoparticles for glucose electrocatalytic oxidation. (10th September 2017) - Ji, Yaqiang; Liu, Jiao; Liu, Xiaonan; Yuen, Matthew M.F.; Fu, Xian-Zhu; Yang, Ying; Sun, Rong; Wong, Ching-Ping
Graphical abstract: Highlights: 3D hierarchically porous Cu@Cu2 O films are fabricated by a facile method. Pd nanoparticles are in-situ grown on the 3D hierarchical porous Cu-Cu2 O films. Porous Cu@Cu2 O-Pd electrodes demonstrate excellent electrocatalytic activity for glucose oxidation. Abstract: 3D hierarchically porous Cu@Cu2 O films supported Pd nanoparticles with excellent electrocatalytic activity are synthesized through electrochemical deposition, anodic oxidation and redox growth. Enzyme-free glucose biosensors based on the porous Cu@Cu2 O-Pd electrodes exhibit higher sensitivity (1.157 mA cm −2 mM −1 ) than those of the porous Cu@Cu2 O films (0.607 mA cm −2 mM −1 ), porous Cu films (0.507 mA cm −2 mM −1 ) and Pd nanoparticles (0.107 mA cm −2 mM −1 ). The enhanced activity of the porous Cu@Cu2 O-Pd nanostructures might be attributed to the unique hierarchical porous structures with highly exposed active sites and synergetic effect from metal oxide semiconductor Cu2 O and noble metal Pd.